2020
DOI: 10.3390/nu12082409
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Fermented Rice Bran Attenuates Muscle Atrophy in a Diabetic Rat Model

Abstract: Fermented rice bran (FRB), a prospective supplement, has been proven to ameliorate certain medical conditions. However, its nutraceutical effect on muscle atrophy has never been investigated. The present study aimed to evaluate the effect of FRB on muscle atrophy in a streptozotocin (STZ)-induced diabetic rat model. Three groups of Sprague-Dawley rats, namely the control, STZ, and FRB groups, were treated as follows. The diabetic groups (STZ and FRB) were injected intraperitoneally with STZ (40 mg/kg BW), wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Diabetic skeletal muscle atrophy, defined by decreased skeletal, and muscular strength, and mass, is a common complication of diabetes called diabetic myopathy [1]. Diabetic myopathy contributes to the development of complications and other comorbidities of diabetes [4] and is considered a significant clinical challenge associated with a reduced quality of life [5].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic skeletal muscle atrophy, defined by decreased skeletal, and muscular strength, and mass, is a common complication of diabetes called diabetic myopathy [1]. Diabetic myopathy contributes to the development of complications and other comorbidities of diabetes [4] and is considered a significant clinical challenge associated with a reduced quality of life [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that 5% of FRB supplementation could attenuate metabolic syndrome [ 25 ] and obesity [ 35 ]. Muscle atrophy [ 26 ] and intestinal inflammatory disorders [ 28 ] were also prevented after 10% of RB fermented by A. kawachii and Lactobacillus sp. In the present study, rats in the HF+1% FRB and 5% FRB groups showed significantly lower hepatic IL-1β levels, a decreasing trend of final BWs, plasma leptin levels, and hepatic TNF-α levels compared to the HF group.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, RB has gradually been developed into a low-cost and functional food ingredient. The potential protective effects of FRB against metabolic disorders were investigated in several studies, including METS, hypertension [ 25 ], diabetes [ 26 ], inflammatory bowel disease (IBD) [ 27 , 28 ], and tumor progression [ 29 ], which validated the functional properties of FRB in improving lipid metabolism impairment, regulating glucose levels [ 25 ], suppressing oxidative stress [ 28 ], attenuating inflammatory responses [ 26 , 28 ], and affecting the gut microbiota [ 27 ]. These effects are also involved in regulating NAFLD development.…”
Section: Introductionmentioning
confidence: 99%
“…The change in muscle tissues was observed under a microscope (original magnification 200×). The size of fibers was measured in the image using the ImageJ software () and presented the mean cross-sectional area of the muscle fibers …”
Section: Methodsmentioning
confidence: 99%